Small-scale mining production system design and socio-economic sustainability an application to Philippine gold and copper deposits - Compañero, Reinol Josef DC. (2012)
The nature of the small-scale mining (SSM) or artisanal mining (ASM) industry in the Philippines have seen little development through the years. It is still characterized by rudimentary techniques in the processing of ore deposits leading to various environmental problems, social unacceptability, and still a vast untapped economic potential. One notable observation from a target site, given the nature of Philippine ore, is that only gold is recovered in this level of production and copper is essentially thrown away in the tailings. This study proposed improvements in the technical aspect of minerals processing and metal extraction, focused on local gold and copper-bearing ores, modified the existing production model and introduced an applicable technology which can promote sustainable improvement in the economic, environmental and social aspects of small-scale mining. The central concern dealt with in the current production scheme was the use of mercury (Hg) and Cyanide (CN-); issues arising from utilizing these reagents are already well-documented. A production system design based on flotation technology has been chosen as the better alternative for gold recovery due to its recent development for the said application as well as the advantage of proven functionality for copper recovery -- resulting in an addition of another stream of saleable product.
It was found out that though the rate of metal (Au) production was still faster for cyanidation and amalgamation, flotation can match it in terms of efficiency (amount recovered), operating costs (cheaper reagents input), and another value-adding product in the form of copper (mixed sulfides). Another benefit was the prospect of integration of both Au and Cu production schemes. In addition to the abovementioned design, the combination of Multiple Accounts Analysis (MAA) and Analytical Hierarchy Process (AHP)_ were used to compare the existing and suggested production models in terms of triple bottom line sustainability accompanied by basic Cost-of-Production Analysis using Capital Expenses (CAPEX) and Operating Expenses (OPEX) evaluation resulting to a Define - Quantify - Decide framework. The proposed energy of metrics was found to be useful in evaluating production systems where sustainability is a concern. A sensitivity analysis was also done on tools if applicable to highlight different stakeholder views and to show that the proposed change in the method of production is beneficial. The new production model finds its strength in the environmental and social sustainability aspect as a result of the elimination of by and large issues associated with the hazardous chemicals. As a consequence of the new production system, initiatives pertaining to possible interventions by key groups were also suggested.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman
Keywords: Small-scale mining